Cryocoolers 12 2003
DOI: 10.1007/0-306-47919-2_99
|View full text |Cite
|
Sign up to set email alerts
|

Operation of a Sunpower M87 Cryocooler in a Magnetic Field

Abstract: The Alpha MagneticSpectrometer-02 (AMS-02) is an experiment that will be flown as an Motion of the compressor and displacer pistons through the magnetic field spatial gradients will generate eddy currents. Additional eddy currents are created during magnet charge, discharge, and quench by the time-varjing magnetic field. The results of tests to determine the magnitude of the forces, torques, and heating effects, as well as the need for additional magnetic shielding, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Using their model of the AMs-02 magnet, SCL generated values of the magnetic field along the three axes at 50 grid points specified for each cryocooler (see Figure 1). [2] Before embarking on testing at MIT, the magnetic field values given in AMs-02 coordinates were translated to values in a cryocooler-based coordinate system.…”
Section: Co-ordinate Transformation Of the Ams-02 Field To A Cryocoolmentioning
confidence: 99%
“…Using their model of the AMs-02 magnet, SCL generated values of the magnetic field along the three axes at 50 grid points specified for each cryocooler (see Figure 1). [2] Before embarking on testing at MIT, the magnetic field values given in AMs-02 coordinates were translated to values in a cryocooler-based coordinate system.…”
Section: Co-ordinate Transformation Of the Ams-02 Field To A Cryocoolmentioning
confidence: 99%
“…The coolers are qualified and tested by a team at NASA Goddard Space Flight Center, and are expected to remove a total of approximately 12 W at around 68 K. One of the initial concerns over the cryocoolers was whether their operation or performance would be compromised by the presence of the magnetic field. However, recent testing carried out by NASA [6] has demonstrated that the cryocoolers can be operated without problems or degradation in the stray field generated by the magnet.…”
Section: ) Cryocoolersmentioning
confidence: 99%
“…The four coolers, each capable of 6 to 7 watts of heat lift at 77 K, will be run at reduced power to provide a total of 20-25 W of cooling on the shield at 77 K. The coolers, operating in the stray field of the magnet system, are being specially qualified for operation in a magnetic field of 750-1000 gauss. 31,32 Gifts. The Geosynchronous Imaging Fourier Transform Spectrometer (GIFTS) instrument is an advanced weather observing instrument originally scheduled to be launched on NASA's New Millennium Earth Observing 3 (EO3) spacecraft in 2005.…”
Section: Cryocooler Development For Future Nasa Missionsmentioning
confidence: 99%